Whole-cell immobilization of entercoccus faecium DMF78 by gel entrapment for the direct lactic acid production from sago starch - Duque, Sheba Mae Magbanua (2009)
Enterococcus faecium DMF78 is a novel amylolytic lactic acid bacterium that has the ability to directly convert starch into L(+)-lactic acid. To further improve the lactic acid production, this bacterium was immobilized using three matrices, namely: agar, alginate and K-carrageenan. Each matrix was optimized to maximize lactic acid production. As for agar, the effects of agar quality, NaCl and agar concentrations were investigated. For alginate, the effects of calcium chloride concentration, hardening time and alginate concentration were tested, and for k-carrageenan, the effects of potassium chloride concentration and extended curing time with calcium chloride were studied. The lactic acid production using the above matrices, as optimized, was compared and lactic acid produced was determined using high performance liquid chromatography (HPLC). Data showed that the use of 3% alginate, extruded drop wise on 0.2 M CaCl2, and cured for 1 hour was the most efficient immobilizing matrix for E. faecium DMF78. Tests for reducing sugar and residual starch and estimation of cell wash-out were also determined. A yield of 3.011 g/L lactic acid was observed using E. faecium DMF78 immobilized in alginate, after 24 hours fermentation of sago starch. This can also be expressed as lactic acid productivity of 0.125 g.L-1.h-1 and a lactic acid yield (conversion) of 25.42%